PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO BUKU GRAMEDIA PANDANARAN SEMARANG - Ratih Nadya Atika, 14.05.51.0243; Wuryan, Sophiyanto (Students' Journal of Economic and Management, 2018)
Customer purchasing behavior is unique because of the preference of everyone to a different things. It is influenced by many factors, including product, price, service quality, distribution, promotion and others. The puspose of this study was to analyze the effect of product, price, distribution and promotions on purchasing decisions at Gramedia Pandanaran Semarang Bookstrore, either partially or simultaneously. The result of the analysis can be concluded that: product has positive influence on purchase decisions. Price variable has positive influence on purchase decisions. Distribution variable has positive influence on purchase decisions. Promotion variable has a negative influence on purchase decisions. It is known that the value of Adjusted R Square is 0,281 which means that 28,1% of variation of purchasing decision can be explained by Product, price, distribution and promotion. Product, price, distribution and promotion has a positive influance jointly on purchasing decisions.Keywords: Product, Price, Distribution and Purchasing Decisions